Exploring preferences for the communication of uncertainty in Clinically Isolated Syndrome - Crouch, Millie (2024)
Background: There is inherent uncertainty with a diagnosis of Clinically Isolated Syndrome (CIS), which can result in psychological distress for patients. This uncertainty and distress can be compounded by the way clinicians communicate the diagnosis. This study explored preferences for the communication of uncertainty in CIS, from the perspective of people with CIS and their spouses.